The aDNA Revolution Moves Beyond Genetics - Fauvelle, Mikael ; 0000-0002-0228-9245 (ARCHAEOLOGIA AUSTRIACA, 2025)
Ancient DNA has revolutionized the fields of archaeology and anthropology. Nowhere is this more apparent than in the field of kinship studies. This report provides a reflection on a recent workshop focused on exploring non-biological kinship in light of recent aDNA research. It presents a summary of reflections by workshop participants that emphasized the importance of interdisciplinary collaboration for future research on ancient kinship.